2000
DOI: 10.1002/1098-2744(200009)29:1<17::aid-mc3>3.3.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Reduced global genomic repair of ultraviolet light–induced cyclobutane pyrimidine dimers in simian virus 40–transformed human cells

Abstract: The p53 tumor-suppressor gene has been implicated in the inducible activation of excision repair of ultraviolet (UV)-induced cyclobutane pyrimidine dimers (CPDs) in human cells. Because the large T antigen (LTAg) of the simian virus 40 (SV40) binds p53 protein and can interfere with its function, it was of interest to study DNA repair in normal human fibroblasts that had been transformed by SV40 compared with that in their nontransformed parental counterparts and to determine whether such transformation attenu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
12
0
1

Year Published

2001
2001
2006
2006

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(14 citation statements)
references
References 0 publications
1
12
0
1
Order By: Relevance
“…Although in such techniques the cells are prelabeled with very low activities of [ 3 H]dThd, typically between 0.1 and 1 mCi/ml (Mirzayans et al, 1996;Ford et al, 1998;Hwang et al, 1999;Bowman et al, 2000;Smith et al, 2000), we have shown here that prelabeling of NHFs with 0.05 mCi/ml [ 3 H]dThd (stock specific activity, 5 Ci/mmol) results in nuclear accumulation of p53 and growth arrest (Figures 1 and 2). Our studies further demonstrate that, unlike labeling with [ 3 H]dThd, labeling of human cells with [ 14 C]dThd for 24 h does not produce any effect on proliferation (Figure 1), p53 protein levels (Figure 3 and data not shown), or CPD repair (data not shown).…”
Section: Discussionmentioning
confidence: 51%
See 1 more Smart Citation
“…Although in such techniques the cells are prelabeled with very low activities of [ 3 H]dThd, typically between 0.1 and 1 mCi/ml (Mirzayans et al, 1996;Ford et al, 1998;Hwang et al, 1999;Bowman et al, 2000;Smith et al, 2000), we have shown here that prelabeling of NHFs with 0.05 mCi/ml [ 3 H]dThd (stock specific activity, 5 Ci/mmol) results in nuclear accumulation of p53 and growth arrest (Figures 1 and 2). Our studies further demonstrate that, unlike labeling with [ 3 H]dThd, labeling of human cells with [ 14 C]dThd for 24 h does not produce any effect on proliferation (Figure 1), p53 protein levels (Figure 3 and data not shown), or CPD repair (data not shown).…”
Section: Discussionmentioning
confidence: 51%
“…Metabolic labeling of human cells with [ 3 H]dThd is commonly used in DNA repair assays (Mirzayans et al, 1996;Ford et al, 1998;Hwang et al, 1999;Bowman et al, 2000;Smith et al, 2000). Since we demonstrated here that [ 3 H] labeling induces nuclear accumulation of p53, and because p53 is known to influence nucleotide excision repair (Wang et al, 1995), we determined the impact of radiolabeling on the repair of UV-induced CPDs.…”
Section: Effect Of Radiolabeling On Cell Growth and Clonogenic Survivalmentioning
confidence: 99%
“…This difference may be due to the analysis of primary cell lines compared with transformed cells. In these immortalized cells, p53 function is compromised, affecting the removal of cyclobutane pyrimidine dimers from genomic DNA, in addition to other pathways (12,13). Cells from CS patients mutated in either the CSA or CSB gene (14) show no defect in Chk1 and p53 phosphorylation, whereas XP-A fibroblasts (15) are defective in activating the checkpoint after UV irradiation, compared with normal and CS fibroblasts (Fig.…”
Section: Checkpoint Activation In G0 and G2͞m Fibroblasts Depends On mentioning
confidence: 97%
“…In fact, a significant number of physiological changes after viral transformation have been reported. For example, loss of p53 function with consequent alteration in cell cycle control (24) decreased DNA repair (25,26), and diminished catalase activity (27) was found.…”
mentioning
confidence: 99%